Assessing Rwexit: the impact and implications of Rwanda’s withdrawal of its article 34(6)-declaration before the African Court on Human and Peoples’ Rights (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2022)
ABSTRACT: This article reviews and analyses Rwanda’s withdrawal of the declaration that allows individuals and NGOs direct access to the African Court of Human and Peoples’ Rights, pursuant to article 34(6) of the African Court Protocol, which is a first in the young life of the preventing those accused of genocide minimisation or denial from accessing the African Court, thus seemingly attempting to deny certain Rwandans an avenue to assert their rights. The article further argues that, faced with the first prominent challenge to its authority, the African Court produced a wellreasoned decision that allows withdrawal but only after a 12-month cooling off period. What is of more concern is what appears to be a six-month delay in rendering the publicly available decision, which is unfortunate especially in the context of an envisaged 12-month cooling-off period. The article concludes by noting that any concerns of a flood of similar withdrawals has yet to occur, but adds that the decision puts the African Court in good stead to consider similar applications, as long as the African Court adheres to a stricter timeline for the publication of such decisions. TITRE ET RÉSUMÉ EN FRANCAIS: Evaluation du Rwexit: impact et conséquences du retrait par le Rwanda de sa déclaration de reconnaissance de la juridiction de la Cour africaine des droits de l’homme et des peuples faite aux termes de l’article 34(6)RÉSUMÉ: Cet article examine le retrait de la déclaration du Rwanda autorisant les individus et les Organisations Non Gouvernementales à saisir directement la Cour africaine des droits de l'homme et des peuples, conformément à l'article 34(6) du Protocole à la Cour africaine. Ce retrait est une première dans la vie de la jeune juridiction et qui aurait pour but d’empêcher les personnes accusées de minimisation ou de négation du génocide d’avoir accès à la Cour africaine et apparait visiblement, par conséquent, comme une tentative de dénier à certains Rwandais une voie de recours pour faire valoir leurs droits. Cet article avance en outre que, confrontée au premier défi majeur à son autorité, la Cour africaine a rendu une décision bien motivée qui autorise le retrait, mais seulement après un délai de 12 mois, considéré comme un préavis. Ce qui est plus préoccupant est le retard de six mois mis pour rendre l’arrêt disponible au public, un fait regrettable eu égard particulièrement à l’option d’un retrait assorti d’un délai de préavis de 12 mois. L'article conclut en notant que la crainte d’une multiplication de retraits similaires ne s’est pas encore réalisée mais ajoute que la décision qu’elle a rendue met la Cour en état d’examiner des demandes similaires pour autant que de telles décisions soient publiées dans des délais plus strictes.
Keywords: African Court on Human and Peoples’ Rights; African Charter on Human and Peoples’ Rights; Rwanda; article 34(6)-declaration; direct access; fair trial